Optimization of Circular Plate Separators with Cross Flow for Removal of Oil Droplets and Solid Particles - Ngu, Hei; Wong, Kien Kuok; Law, P.L (Water Environment Federation, 2012)
A circular gravity-phase separator using coalescing medium with cross flow was developed to remove oil and suspended solids from wastewaters. Coalescence medium in the form of inclined plates promotes rising of oil droplets through coalescence and settling of solid particles through coagulation. It exhibits 22.67% higher removal of total suspended solids (TSS) compared to separators without coalescing medium. Moreover, it removed more than 70% of oil compared to conventional American Petroleum Institute separators, which exhibit an average of 33% oil removal. The flowrate required to attain an effluent oil concentration of 10 mg/L (Qo10) at different influent oil concentrations (Cio) can be represented by Qo10 3 1025 5 20.0012Cio + 0.352. The flowrate required to attain an effluent TSS concentration of 50 mg/L (Qss50) at different influent TSS concentrations (Ciss) can be represented by Qss50 3 1025 5 1.0 3 106 Ciss 22.9576. The smallest removable solid particle size was 4.87 mm. Water Environ. Res., 84, 299 (2012).